2022
DOI: 10.1021/acs.energyfuels.2c01025
|View full text |Cite
|
Sign up to set email alerts
|

Serpentine Ni3Ge2O5(OH)4 Nanosheets Grow on Porous Mo2N for an Efficient Oxygen Evolution Reaction

Abstract: Transition-metal-based layered serpentine materials are promising as cheap and active electrocatalysts for the oxygen evolution reaction (OER). However, the serpentine materials have poor conductivity and chemical stability, which induce that the activity and stability of these materials are not favorable. Herein, Ni3Ge2O5(OH)4 nanosheets are designed to grow on highly conductive porous Mo2N materials to form composite catalysts for the electrochemical OER. The fabrication of Mo2N/Ni3Ge2O5(OH)4 is achieved via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It is revealed that the mixed valence of co-catalysts is more favorable for photocatalytic water oxidation. Zhang’s group presented serpentine Ni 3 Ge 2 O 5 (OH) 4 nanosheets on porous Mo 2 N for an efficient oxygen evolution reaction . Zhang and his co-workers reported a defect management strategy on SrNbO 2 N through Zn modification for promoted photocatalytic water oxidation .…”
Section: Photooxidationmentioning
confidence: 99%
“…It is revealed that the mixed valence of co-catalysts is more favorable for photocatalytic water oxidation. Zhang’s group presented serpentine Ni 3 Ge 2 O 5 (OH) 4 nanosheets on porous Mo 2 N for an efficient oxygen evolution reaction . Zhang and his co-workers reported a defect management strategy on SrNbO 2 N through Zn modification for promoted photocatalytic water oxidation .…”
Section: Photooxidationmentioning
confidence: 99%
“…It is well known that noble metal-based materials such as IrO 2 and RuO 2 are among the most active electrocatalysts for OER . However, high cost and scarcity are significant barriers to the large-scale application of noble metals for electrocatalytic water splitting. , Therefore, it is crucial to design and construct active and stable materials as an alternative to noble metal-based electrocatalysts. …”
Section: Introductionmentioning
confidence: 99%